Risk Factors of Dengue Fever Outbreak in Karo District, North Sumatera, Indonesia - Frans Yosep Sitepu (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2019)
Dengue fever (DF) infection continues to present a seriuos public health problem in North Sumatera, Indonesia. A DF outbreak was reported in Merek Sub-district, Karo District which is one tourist destination in North Sumatera during April-May 2017. An epidemiological investigation was conducted to identify the risk factors and recommend control measures. An observational study with a matched case control design was conducted. A case was defined as any resident of Merek sub-district who had suffer major clinical symptoms of DF such as fever, severe headache, pain behind eyes, muscle and joint pains, and rash from April – May, 2017. A control was defined as neighbors of cases who did not have clinical signs and symptoms of DF and were matched for age and sex. We interviewed 37 cases and 37 controls. Age cases ranged from 2 year to 37 years (median= 12 years). The multivariate analyses showed that presence of mosquito breeding sites (OR=4.87, 95%CI=1.33-17.85) and habit of hanging worn clothes (OR=5.12, 95%CI=1.25-21.03) were significant risk factors. It is recommended to eliminate mosquito breeding sites routinely, avoid habit of hanging worn clothes, and conduct strict surveillance of DF continously.